ANALYSIS OF STUDENTS' ERRORS IN SOLVING PLANE GEOMETRY WORD PROBLEMS BASED ON NEWMAN’S ERROR ANALYSIS (NEA) METHOD - Syawali, dinda Sholehah; Mulyawati, Ima (Prima: Jurnal Pendidikan Matematika, 2024)
This study aims to apply Newman's Error Analysis (NEA) as a method for teaching students to identify mistakes they make when solving word problems involving plane geometry, identify factors that contribute to students' difficulty in understanding mathematical concepts while solving such problems, and determine appropriate strategies to address errors made by students in solving plane geometry word problems. The research used descriptive methodology and is classified as qualitative research. Data was obtained through tests and interviews conducted with four Grade IV students from a public elementary school in East Jakarta who participated in the study as respondents. The students' errors in solving plane geometry word problems using the NEA method were attributed to several factors: lack of attention during class, unawareness of the main issues in the problem, difficulty in selecting appropriate mathematical operations, challenges in executing calculation procedures accurately, and neglecting to review final answers. To address these errors, the research recommends providing practice questions ranging from easy to difficult, using teaching techniques and delivery methods that are easily understood by students, and using a variety of learning methods to accommodate different learning styles among students.Keywords: NEA, factors causing errors, error handling efforts